Teres ligament patch reduces relevant morbidity after distal pancreatectomy (the DISCOVER randomized controlled trial) - Hassenpflug, Matthias; Hinz, Ulf; Strobel, Oliver; Volpert, Johanna; Knebel, Phillip; Diener, Markus K.; Dörr-Harim, Colette; Werner, Jens; Hackert, Thilo; Büchler, Markus W. (Annals of surgery, 2016)
Objective:The aim of this study was to analyze the impact of teres ligament covering on pancreatic fistula rate after distal pancreatectomy (DP).Background:Postoperative pancreatic fistula (POPF) represents the most significant complication after DP. Retrospective studies suggested a benefit of cove
Gesehen am 04.05.2020